Diseño de recuperador de reloj y datos para un canal serial de alta velocidad en un entorno de simulación de señal mixta - Carmona-Cruz, Allan Gerardo (Instituto Tecnológico de Costa Rica, 2018)
The ITCR is developing a project for the simulation of a high-speed serial link at behavioral level in a mixed signal simulation environment. An important section of it is the development of a clock and data recovery (CDR) between the transmitter and the receiver that allows synchronization in communication. In this work you will see the process of selection and design of the CDR. In addition, correct operation was veri ed through simulations.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: CDR; Offset; Frecuencia; Detectores; Diagramas; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics